TOURISM SECTOR PERFORMANCE ON INDONESIA’S ECONOMIC GROWTH - Happy Febrina Hariyani (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2018)
Tourism is believed to be a booster for economic growth in developing countries. The tourism sector in Indonesia is one of the sectors that has the highest contribution in foreign exchange to the economy. Tourism activity in the form of export trade in services is the only sector that constantly make a positive contribution in the balance of trade in services in Indonesia. This study aims to analyze the influence of tourism consumption, tourism investment and government spending to economic growth. The results of this study indicate that, in the long run, those variables affect economic growth. While in the short run, they do not influence economic growth.